An examination of the quality of wireless signal at access points based on the kind of obstacle - Hendra Ginanjar; Ritzkal Ritzkal; Yuggo Afrianto (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2023)
The purpose of this study is to analyze the wireless signal quality of an access point (AP) with a focus on the types of obstacles that could potentially affect network performance. The use of wireless technology has become essential in sustaining modern civilization, especially in environments with various types of machines such as walls, electronic devices, and electromagnetic machines. The analysis method involves measuring and adjusting the signal quality at several points that indicate conditions that could be affected by the use of non-reversible mesh. The signal strength, transmission speed, and connection handling at each observation point were analyzed. Finally, the analysis results were used to identify the type of wireless signal work and the impact of different types of obstacles. The results of this study provide insight into how certain types of obstacles can affect wireless signal quality at access points. These findings can aid in the development of strategies to improve and enhance wireless network performance, including recommendations for optimizing access point placement or using interference mitigation technologies.